THE EFFECT OF RED GUAVA JUICE AND DRAGON FRUIT JUICE ON HEMOGLOBIN LEVELS IN THIRD TRIMESTER PREGNANT WOMEN AT MANDALAWANGI HEALTH CENTER - Masnu’ah, Siti; Barkah, Asep (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The aim of this research is to determine the influence of red guava juice and dragon fruit juice on the increase of hemoglobin levels in pregnant women with anemia in the Mandalawangi Public Health Center area in 2023. The research design employed is a quasi-experimental design with a pretest and posttest without a control group design, specifically a quasi-experimental design dividing participants into two groups: the red guava juice group and the dragon fruit juice group. Both groups undergo a pre-test before the experiment is administered and a post-test afterward. The hypothesis of this study investigates whether there is an effect of administering a combination of red guava juice and dragon fruit juice on the increase of hemoglobin levels in pregnant women with anemia in the Mandalawangi Public Health Center area.